Orson Welles, theatrical character. A scenic biography and a cinematographic testimony about it - Pérez Bowie, José Antonio (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
I am dealing in these pages with a curious sample of the multifaceted relationships between the fields of theater and cinema. Filmmaker Orson Welles stars in a stage biography written by American playwright Richard France. This theatrical piece is the subject of a staging directed by Esteve Riambau, who, in turn, directs a documentary film that narrates the various phases of the process to transfer the text to the stage and where a corpus of theoretical reflections on this process by the leading actor (José M.ª Pou) and of other people involved in it, including the author himself. The theatrical text, its staging (with the variants introduced by its manager) and the cinematographic documentary around it are successively analyzed.
Keywords: cinema-theater relations; biographical theater; staging; biopic; Orson Welles; Richard France; Esteve Riambau; José M.ª Pou